Integrating Conceptual Change Text and Concept Mapping to Teach Cellular Respiration Concepts to the First Secondary Scientific Stream Students' - Al khawaldeh, Salem (Jordan Journal of Educational Sciences, 2007)
The study aimed at investigating the effectiveness of conceptual change text, concept mapping, and a combination of conceptual change text/concept mapping on the first secondary scientific stream students' understanding of cellular respiration, and their retention of this understanding compared to the traditional instruction. Using information collected through interviews and related literature, the Cellular Respiration Concept Test was developed, and administered as a pre-test, post-test, and a retention test to a total of (164) first secondary scientific stream students in 4 sections at a school in an ubran area. The sections were randomly assigned as a control and three experimental groups. Students in the first experimental group (n = 40) received conceptual change text instruction; students in the second experimental group (n = 41) received concept mapping instruction; students in the third experimental group (n = 41) received conceptual change text and concept mapping instruction; and students in the control group (n = 42) received traditional instruction. The results indicated the conceptual change text, concept mapping and conceptual change text/concept mapping treatment groups significantly outperformed the traditional treatment group in conceptual understanding of cellular respiration, and in the retention of this understanding. However, there was no statistically significant difference among the three experimental groups. A number of recommendations were derived from the findings of this study.